SAHABAT NABI DALAM PANDANGAN TAFSIR AL-QUMMI - Pratomo, Hilmy (LP3M Universitas Sains Al Qur'an, 2024)
ABSTRACT The background of this research is based on the importance of understanding the interpretation of the Prophet's friend in tafsir literature to enrich insight into the development of tafsirs in Islamic tradition, especially in the Shia context. The most famous of the Shiites is Abu al-Hasan Ali bin Ibrahim al-Qummi. This study aims to examine the views of Prophet Muhammad's friend in Tafsir al-Qummi. The research methods used are qualitative methods with a descriptive-analytic approach. Data was collected through library studies of Tafsir al-Qummi's texts as well as other relevant supporting literature. The analysis is done by identifying and categorizing the verses of the Qur'an that represent the views presented by al-Qummi about the Prophet Muhammad. The results of the research show that the Tafsir al-Kummi gives a specific and sometimes controversial view of some Prophet Mohammed friends. Al-Qommi often quotes the hadiths of the Shia priests, especially his own father to support his interpretation. Some friends were praised for their loyalty and contributions to Islam, while others were criticized for acts or views that were considered to deviate from the teachings of the Prophet. The conclusion of this study is that al-Qummi's interpretation reflects a typical theological perspective of the Shiite tradition on Prophet Muhammad's friend. This research has made an important contribution to understanding the dynamics of Prophet's friends' interpretation in Tafsir literature and highlights the differences between Shiite and Sunni interpretations. These findings are expected to be a reference for further research in the field of interpretation. Keywords: Companions of the Prophet, Syiah and Tafsir al-Qummi ABSTRAK Latar belakang penelitian ini didasarkan pada pentingnya memahami interpretasi sahabat Nabi dalam literatur tafsir untuk memperkaya wawasan tentang perkembangan tafsir dalam tradisi Islam, khususnya dalam konteks Syiah. Kitab tafsir yang masyhur di kalangan Syiah adalah Tafsir al-Qummi karya Abu al-Hasan Ali bin Ibrahim al-Qummi. Penelitian ini bertujuan untuk mengkaji pandangan terhadap sahabat Nabi Muhammad dalam Tafsir al-Qummi. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan deskriptif-analitis. Data dikumpulkan melalui studi pustaka terhadap teks Tafsir al-Qummi serta literatur pendukung lainnya yang relevan. Analisis dilakukan dengan cara mengidentifikasi dan mengkategorikan ayat al-Qur’an yang merepresentasikan pandangan-pandangan yang disampaikan oleh al-Qummi mengenai sahabat Nabi Muhammad. Hasil penelitian menunjukkan bahwa Tafsir Al-Qummi memberikan pandangan yang spesifik dan terkadang kontroversial mengenai beberapa sahabat Nabi Muhammad. Al-Qummi sering mengutip hadis-hadis dari para Imam Syiah, terutama ayahnya sendiri untuk mendukung interpretasinya. Beberapa sahabat dipuji karena kesetiaan dan kontribusinya terhadap Islam, sementara yang lain dikritik karena tindakan atau pandangan yang dianggap menyimpang dari ajaran Nabi. Simpulan dari penelitian ini adalah bahwa tafsir al-Qummi mencerminkan perspektif teologis yang khas dari tradisi Syiah terhadap sahabat Nabi Muhammad. Penelitian ini memberikan kontribusi penting dalam memahami dinamika interpretasi sahabat Nabi dalam literatur tafsir dan menyoroti perbedaan pandangan antara tafsir Syiah dan Sunni. Temuan ini diharapkan dapat menjadi referensi bagi penelitian selanjutnya dalam bidang studi tafsir. Kata Kunci: Sahabat Nabi, Syiah dan Tafsir al-Qummi